Pyroelectric Janus nanomotors for synergistic electrodynamic-photothermal-antibiotic therapies of bacterial infections. (May 2023) - Meng, Jie; Zhang, Peng; Liu, Qingjie; Ran, Pan; Xie, Shuang; Wei, Junwu; Li, Xiaohong
Abstract: Antibacterial electrotherapy is currently activated by external electric field or self-powered generators, but usually needs complicated power management circuits. Herein, near-infrared illumination (NIR) of pyroelectric nanoparticles (NPs) produces a built-in electric field to address the effectiveness and safety concerns in the antibacterial treatment. Janus tBT@PDA NPs were obtained by capping polydopamine (PDA) on tetragonal BaTiO3 (tBT) NPs through defining the polymerization time, followed by ciprofloxacin (CIP) loading on the PDA caps to fabricate Janus tBT@PDA-Cip NPs. NIR illumination of PDA caps creates temperature variations on tBT NPs to generate photothermal and pyroelectric effects. Finite element simulation reveals a pyroelectric potential of over 1 V and sufficient reactive oxygen species (ROS) are produced to exhibit pyroelectric dynamic therapy (PEDT). The elevated temperature on one side of the Janus NPs produces thermophoretic force to drive NP motion, which enhances interactions with bacteria and overcomes limitations in the short action distance and lifespan of ROS. The pyroelectric field accelerates CIP release through weakening the π-π stacking and electrostatic interaction with PDA and also interrupts membrane potentials of bacteria to enhance CIP invasion into bacteria. The synergistic antibacterial effect of pyroelectric tBT@PDA-Cip NPs causes the fully recovery of S. aureus -infected skin wounds and regeneration of intact epidermis, blood vessels and hair follicles, while no obvious pathological change or inflammatory lesion is detected in the major organs. Thus, the pyroelectric Janus nanomotors demonstrate synergistic PEDT/photothermal/antibiotic effects to enhance antibacterial efficacy while avoiding the necessity of excessive heat, ROS and antibiotic doses. Statement of significance: Antibacterial treatment is challenged by antibiotics-derived side effects and the evolution of resistant strains. Phototherapy is commonly associated with excessive heat and oxidative stress, and their combinations with other agents are especially encouraged to strengthen antibacterial efficacy while alleviating the associated side effects. Electric field is another activator to generate antibacterial abilities, but usually requires complicated power management and bulk electrodes, making it inconvenient in a biological setup. To address these challenges, we propose a strategy to generate microelectric field on nanoparticles themselves and achieve synergistic electrodynamic-photothermal-antibiotic therapies. The pyroelectric effect weakens interactions between nanoparticles and antibiotics to accelerate drug release, and the built-in pyroelectric field increases membrane fluidity to enhance bacterial uptake of antibiotics. Graphical Abstract: Image, graphical abstract